ANALISIS PERBANDINGAN KINERJA REKSA DANA SAHAM DAN REKSA DANA TERPROTEKSI DENGAN MENGGUNAKAN METODE SHARPE DAN METODE TREYNOR - Betari Ayu Kumala Sari Dewi (Jurnal Ilmiah Mahasiswa FEB, 2017)
This research aims to determine the comparison of the performance of equity fund and protected fund. The methods used in measuring the performance of mutual fund are Sharpe and Treynor methods. The population in this research consists of all equity fund and protected fund for non syariah companies that have been listed during 2013 until 2016 years. Sampling in this research using purposive sampling method that obtained a sampel of 70 equity funds and 33 protected funds with a total of 103 mutual funds. The results of this research indicate that there is a significant difference between the performance of equity fund and protected funds by using Sharpe method and Treynor method. This is justified by Mann-Whitney test by obtaining P value < 0.05. The implication in this research is shown to the investor to choose mutual fund investment using Sharpe method by taking into account the total risk. The investment manager should consider appropriate asset allocation to the performance of equity fund and protected fund.  Keyword: Equity Fund, Protected Fund, Sharpe Method, Treynor Method